2021
DOI: 10.1016/j.ypmed.2021.106547
|View full text |Cite
|
Sign up to set email alerts
|

Suicide prevention in the covid-19 era

Abstract: The COVID-19 pandemic is affecting the health of people all around the world including mental health as social isolation which has been one of the best infection mitigation efforts is strongly associated with anxiety, depression, self-harm and suicide attempts. These feelings are consistent with past pandemics where there was loss of routine and sociability. Suicidality has been on the rise in the United States and it is within this context that the pandemic has struck. With the risk of suicide being increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…A clinical trial found telepractice to be as feasible as traditional in-office clinical care delivery if there is accordance with safety plans, training, and published guidelines ( Luxton et al, 2014 ). Telehealth was deemed as useful in continued psychiatric care during the COVID-19 pandemic especially for postvention ( Rothman and Sher, 2021 ). A systematic review and random-effects meta-analyses of brief contact interventions (letter, postcard, telephone, green card or crisis card) for reducing self-harm, suicide attempt, and suicide recommended well-designed trials in clinical populations ( Milner et al, 2015 ).…”
Section: Current State Of the Art – Digital Tools And Technologymentioning
confidence: 99%
“…A clinical trial found telepractice to be as feasible as traditional in-office clinical care delivery if there is accordance with safety plans, training, and published guidelines ( Luxton et al, 2014 ). Telehealth was deemed as useful in continued psychiatric care during the COVID-19 pandemic especially for postvention ( Rothman and Sher, 2021 ). A systematic review and random-effects meta-analyses of brief contact interventions (letter, postcard, telephone, green card or crisis card) for reducing self-harm, suicide attempt, and suicide recommended well-designed trials in clinical populations ( Milner et al, 2015 ).…”
Section: Current State Of the Art – Digital Tools And Technologymentioning
confidence: 99%
“…The COVID-19 pandemic is also responsible for increased consumption of stimulants, including alcohol (Calina et al, 2021) and drugs (Dubey et al, 2020). In addition, an increased risk of suicide in the population was noted during this period and an increase in suicide rates was reported as a negative impact of the quarantine (Rothman, Sher, 2021).…”
Section: Consequences Of a Pandemicmentioning
confidence: 86%
“…The tendency to focus on the worst feared outcomes of suicidality can overshadow findings that compared to before the pandemic, the demographics and reasons behind suicidality have shifted. Specifically, it has been found that women, male youth, single parents, the elderly, and those without previous psychopathology have been at growing risk for suicidality (Dubé et al, 2021;Kim et al, 2022;Rothman & Sher, 2021). This demonstrates that beyond the need for a multidisciplinary understanding of suicide trends at a broader level, interventions and strategies should be tailored to the demographics with the highest risk of suicidality (Holmes et al, 2020).…”
Section: Practical Applicationsmentioning
confidence: 99%